2021
DOI: 10.1158/0008-5472.can-20-3761
|View full text |Cite
|
Sign up to set email alerts
|

TET2 and DNMT3A Mutations Exert Divergent Effects on DNA Repair and Sensitivity of Leukemia Cells to PARP Inhibitors

Abstract: Somatic variants in TET2 and DNMT3A are founding mutations in hematological malignancies that affect the epigenetic regulation of DNA methylation. Mutations in both genes often co-occur with activating mutations in genes encoding oncogenic tyrosine kinases such as FLT3ITD, BCR-ABL1, JAK2V617F, and MPLW515L, or with mutations affecting related signaling pathways such as NRASG12D and CALRdel52. Here, we show that TET2 and DNMT3A mutations exert divergent roles in regulating DNA repair activities in leukemia cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 58 publications
3
34
0
Order By: Relevance
“…In particular, the co-occurrence of FLT3 -ITD and TET2 mutations exacerbated the sensitivity of Lin − CD34 + primary AML cells to olaparib. On the contrary, cells expressing FLT3 -ITD alteration alone or in combination with DNMT3A mutations were resistant to the treatment with the inhibitor [ 135 ]. In line with data form primary samples, mouse models expressing activated-tyrosine kinases ( FLT3 -ITD, JAK2 V617F , MPL W515L , NRA S G12D ) showed that Tet2 -deficient cells were sensitive to PARPi, while Dnmt3a -deficient cells were not.…”
Section: Synthetic Lethality and Parp Inhibitors: A New Therapeutic W...mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the co-occurrence of FLT3 -ITD and TET2 mutations exacerbated the sensitivity of Lin − CD34 + primary AML cells to olaparib. On the contrary, cells expressing FLT3 -ITD alteration alone or in combination with DNMT3A mutations were resistant to the treatment with the inhibitor [ 135 ]. In line with data form primary samples, mouse models expressing activated-tyrosine kinases ( FLT3 -ITD, JAK2 V617F , MPL W515L , NRA S G12D ) showed that Tet2 -deficient cells were sensitive to PARPi, while Dnmt3a -deficient cells were not.…”
Section: Synthetic Lethality and Parp Inhibitors: A New Therapeutic W...mentioning
confidence: 99%
“…Seminal results, that will drive future development, are expected from the combination of PARPi with decitabine (NCT02878785), particularly in the sub-cohort of TET2 and TET2/DNMT3A -mutant AML for their high sensitivity to DNA damage [ 135 ], and from target-restricted studies in IDH1 / 2 mutant (NCT03953898) and in cohesin mutant (NCT03974217) AML. The preclinical evidence reported in IDH1 / 2 [ 142 , 143 , 156 ] or cohesin-mutated AML patients [ 140 , 155 ], as well as other subgroups, seems to promise success for molecularly directed trial designs for PARPi single agent and combination regimens.…”
Section: Clinical Activity Of Parp Inhibitors In Acute Leukemiamentioning
confidence: 99%
“…It remains to be seen whether a similar association between PARP1 and TET1 exists in myeloid neoplasms. Conversely, somatic TET2 deficiency is a common feature of hematologic malignancies and is associated with downregulation of BRCA1 and LIG4, leading to impaired HR and NHEJ, respectively [ 214 ]. Thus, TET2-deficient cells are increasingly reliant on the PARP1-mediated alt-EJ DNA repair pathway, conferring sensitivity to PARPi therapy both in vitro and in vivo [ 214 , 215 ].…”
Section: Parp Inhibitors For the Treatment Of Myeloid Neoplasmsmentioning
confidence: 99%
“…Conversely, somatic TET2 deficiency is a common feature of hematologic malignancies and is associated with downregulation of BRCA1 and LIG4, leading to impaired HR and NHEJ, respectively [ 214 ]. Thus, TET2-deficient cells are increasingly reliant on the PARP1-mediated alt-EJ DNA repair pathway, conferring sensitivity to PARPi therapy both in vitro and in vivo [ 214 , 215 ]. In this manner, TET2 mutations may serve as a biomarker for PARPi sensitivity in epigenetically dysregulated malignancies.…”
Section: Parp Inhibitors For the Treatment Of Myeloid Neoplasmsmentioning
confidence: 99%
“…DSBs are among the most lethal DNA aberrations, and are repaired through either homologous recombination (HR) mediated repair or non-homologous end joining (NHEJ) ( 23 ). Targeting DNA repair pathways for cancer therapy has gained a momentum over the past few years, with poly(adenosine 5’-diphosphate-ribose) polymerase (PARP) inhibition for HR deficient tumors have shown promise in clinical settings ( 2729 ). Therefore, identifying molecular regulation of DNA repair pathways important for AML cell survival is essential for developing effective combination targeted therapy.…”
Section: Introductionmentioning
confidence: 99%